EFEKTIVITAS MEDIA PERMAINAN SUDOKU DALAM MENGHAFAL HURUF KANA (MENGGUNAKAN METODE EKSPERIMEN QUASI TERHADAP SISWA JAPANESE CLUB SMP LABORATORIUM PERCONTOHAN UPI) (THE EFFECTIVENESS OF SUDOKU GAME MEDIA IN MEMORIZING KANA LETTERS (USING QUASI-EXPERIMENTAL METHOD ON STUDENTS OF JAPANESE CLUB SMP LABORATORY PILOT UPI) - Konstantina Adinda Putrilani; Renariah Renariah; Neneng Sutjiati (Jurnal Japanedu: Pendidikan dan Pengajaran Bahasa Jepang, 2016)
When studying Japanese at school, basic aspects must study is the Japanese letter. In its writing system, Japanese has four letters, namely kanji, hiragana, katakana, and roomaji. Before the stage of kanji learning, firstly, students have to learn hiragana and katakana which are commonly called kana. Kana, composed of 96 letters where the letter of the hiragana and katakana are barely different. This causes difficulties for students to learn kana. Therefore, we need a media to facilitate learners to learn kana. One medium that can be used are game as the learning media. This study, the media used is a sudoku game that has been modified. The purpose of this study is to acknowledge students’ ability in learning kana, before and after using the sudoku game as a media. In addition, this study also aims to analyze the influence of sudoku game usage as the media in learning kana Letters, and to find out the students' response to the use of sudoku game as a media. This study uses a quasi experiment method with the one group pre-test - post-test as experiment design. Samples were 20 students from Japanese Club members who were taken from a population of SMP Laboratorum Percontohan UPI Bandung. The instrument used was test, questionnaire and observation. Based on the data analysis, the t value at 6.53. T table at 2.09 on a significance level of 5% and 2.86 at 1% significance level. Thus, the results obtained that t value is greater than t table at a significance level of 5% (6.53> 2.09). This shows that the usage of sudoku game as media is a very effective in learning kana. In addition, based on data analysis of the questionnaire, the respondents gave a positive response to the use of media sudoku game that are attractive, and easy to follow